Respuesta :

Answer:

Step-by-step explanation:

2x + 3y = 13     ------------(i)

4x -y  = -2  ----------------(ii)

(i)           2x + 3y = 13

(ii)*3     12x - 3y = -6       {multiply(ii) by 3}

add,      14x         =  7

                        x = 7/14 = 1/2 = 0.5

                        x = 0.5

Put x = 0.5 in (i)

2*0.5 + 3y = 13

      1 + 3 y = 13

           3y = 13-1

          3y = 12

            y = 12/3

y= 4

Answer:

one solution : (1/2 ; 4)

Step-by-step explanation:

hello :

2x + 3y = 13 ....(*)

4x -y=-2.....(**)

by (**) : y = 4x+2

put this value in (*) : 2x+3(4x+2) =13

2x+12x+6 = 13

14x =7

x=7/14 so: x= 1/2

but : y = 4x+2

y = 4(1/2)+2

y = 4

one solution : (1/2 ; 4)